The Effects of COVID-19 Lockdown on Air Quality in Macedonia - Mirjana Dimovska; Dragan Gjorgjev (Scientific Foundation SPIROSKI, 2020)
BACKGROUND: Faced with the novel coronavirus outbreak (2019-nCoV), various urgent and coordinated actions have been taken worldwide to reduce spread of the disease. Slowing down economic activities, transportation, restrictions of the human public gatherings, and interaction resulted with a tremendous decline in air pollutant concentration especially in nitrogen dioxide, registered by National Aeronautics and Space Administration and European Space Agency satellites. AIM: The aim of the study was to assess the impact of COVID-19 lockdown conditions on the air quality in selected cities in Macedonia. METHODS: Daily mean concentration of the particulate matter (PM10 and PM2.5), nitrogen dioxide, ozone, and carbon monoxide measured in the national air quality monitoring network, was analyzed separately comparing following periods: past week of February 2020 to the end of May 2020 with the same period in 2017–2019. Depending on the data distribution, parametric independent-samples t-test or nonparametric Mann–Whitney U-test was run to determine if there were differences in the pollutants concentration during the COVID-19 and non-COVID-19 period. RESULTS: Implementation of strict restrictions of the movement along with reduced economic activities and vehicular transport, led to notable decrement of air pollutant concentrations. We have found an evident decrease in the concentration levels of all pollutants measured during COVID-19 period in 2020, compared to those from 2017 to 2019 with exceptions for PM2.5 in Kumanovo and carbon monoxide in Skopje (7% and 3% higher concentration). The most notable decrement was for NO2, with a concentration 5–31% lower during COVID-19 period. CONCLUSIONS: Although beneficial to human health, there is a need to assess economic implications of the lockdown that could have a negative impact on the health as well.
Keywords: COVID-19; Lockdown; Effects; Air quality; Air pollution; Macedonia